Characteristics of Pre-Colonial African - Ramuthivheli, Thembinkosi (My University, 2011)
The historical research method was used to characterize management in precolonial Africa. Secondary data sources provided information on African history and pre-colonial leaders. Archival data, relying on published accounts obtainable in libraries and on the World Wide Web were used. Evidence indicates that management existed in pre-colonial Africa: traditional roles and functions of pre-colonial chiefs and kings match current business management activities described in literature. Characteristics of pre-colonial African leaders were comparable to traits defined as necessary for current business managers. Biographies of those pre-colonial African leaders studied also revealed that, as with modern business managers, describing uniform leadership traits common to all successful leaders is difficult. Successful pre-colonial African leaders, like business leaders today, were found to be individuals who did not share a homogenous set of defining characteristics and leadership styles
MBA - WBS
Keywords: Management, African